Effects a multicomponent program on the frailty and quality of life of institutionalized older adults - Yeny Concha-Cisternas; Shlomith Contreras- Reyes; Bastian Monjes; Belen Recabal; Eduardo Guzmán-Muñoz (Revista Cubana de Medicina Militar)
Introduction: Aging is related to a higher prevalence of frailty and deterioration in quality of life. There is also a loss of autonomy, which increases institutionalization. Methodology: Pre-experimental, longitudinal study that evaluated 28 institutionalized older adults (17 women and 11 men). The sample was selected using an intentional non-probabilistic criterion. A multicomponent training program (aerobic resistance, muscular strength, balance and flexibility) was carried out for 6 weeks, before and after the fragility was evaluated based on the phenotype scale proposed by Fried and the quality of life with the World Health Organization questionnaire Quality of Life - Older Adults (WHOQoL-OLD). The Student's t-test was applied to make the comparisons and the effect size was calculated. An alpha level of 0.05 was used. Results: After participating in the multicomponent exercise program, older adults showed significant improvements in the frailty index (p = 0.007; d = 0.36). The quality of life showed statistically significant changes in the dimensions Past, present and future activities (p = 0.018; d = 0.53), Social Participation (p = 0.003; d = 0.53) and Intimacy (p = 0.005; d = 0.36) after completing a multi-component exercise program. The overall quality of life of the participants also showed significant changes (p = 0.007; d = 0.65). Conclusion: A 6-week multi-component physical training program improved the frailty and quality of life of institutionalized older adults.